Investigation of photoluminescence and electrical properties of 3,6-di(9-carbazolyl)-9-(2-ethylhexyl)carbazole - Hotra, Zenon; Stakhira, Pavlo; Volyniuk, Dmytro; Cherpak, Vladyslav; Simokaitiene, Jurate; Tomkeviciene, Ausra; Grazulevicius, Juozas; Kremer, Iryna (Видавництво Львівської політехніки, 2012)
In this paper the photoluminescence of organic semiconductor 3,6-di(9- carbazolyl)-9-(2-ethylhexyl) (TCz1) film and electrical properties of the device on it base are investigated. In the photoluminescence spectrum of TCz1 films at excitation of 320 and 350 nm the new red shifted band appeared which was not observed with the excitation wavelength of 270 nm. An analysis of frequency dependences of the impedance showed that the device ITO/CuI/TCz1/Al can be simulated by an equivalent circuit consisting of two series RC elements representing the organic film bulk and space charge region.
Keywords: Organic light emitting devices; carbazole derivates; impedance spectroscopy; photoluminescence spectra